Pengaruh ROA, CAR, LDR dan BOPO Terhadap Pertumbuhan Laba Pada Bank Umum di Indonesia yang Terdaftar di Otoritas Jasa Keuangan Tahun 2014-2018: The Effect of ROA, CAR, LDR and BOPO on Profit Growth in Commercial Banks Registered in the Financial Services Authority of Indonesia, 2014-2018 - Fitriyah Fitriyah; Dwi Perwitasari Wiryaningtyas; Fajar Wahyu Prianto (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to (1) to determine the effect of ROA, CAR, LDR, and BOPO influence partially to profit growth (2) to know influence of ROA, CAR, LDR, and BOPO influence simultaneously to profit growth (3) to know among ROA , CAR, LDR, and BOPO most dominant effect on profit growth. The method used in this research is quantitative method. The results of research is multiple linear regression equation Y = -31,223 + 261,741 X1 + 9,704 X2 + 6,480 X3 + 24,699 X4 + e. Partially ROA have positive significant effect with value equal to 15,690, equal to 2,014, CAR have not significant effect with value equal to 1,768, equal to 2,014, LDR have significant positive effect with value equal to 3,871, equal to 2,014, BOPO have significant positive effect with value equal to 19,159, equal to 2,014. Simultaneously ROA, CAR, LDR, and BOPO influence to profit growth with value equal to 131,670, equal to 2.58. The most dominant variable in this research is BOPO with value 19,159.